Occupational choice of skilled workers in the presence of a large development sector: Evidence from Sierra Leone - Jamelia Harris (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
Using data from Sierra Leone, I explore the role of cognitive ability in sorting across sectors and the importance of perceptions in the employment decision-making process. Crucial to the analysis is the introduction of the aid-industry/development sector as a 'third sector', which is shown to be attractive to skilled jobseekers. One of the key findings is that the largest share of skilled jobseekers opt for early-career employment working for a donor organisation, INGO, or NGO in the development sector. The results show that cognitive ability matters for occupational choice, as higher ability workers are more likely to choose the development sector over other sectors. Skilled graduates also sort by intrinsic motivations to some extent, but these motivations are secondary to jobseekers' perceptions of various sectors. This result implies that 'mission matching' based on measured preferences may be inhibited in contexts where employment possibilities are limited.
Keywords: J22; J24; F35; C25; 330; development; employment; foreign aid; labour market; occupational choice; Sierra Leone; skilled workers